1971
DOI: 10.1042/bj1250821
|View full text |Cite
|
Sign up to set email alerts
|

The stability of rat liver ribonucleic acid in vivo after methylation with methyl methanesulphonate or dimethylnitrosamine

Abstract: 1. RNA was isolated from rat liver at selected times after the intraperitoneal injection of either [(14)C]methyl methanesulphonate (50mg/kg) or [(14)C]dimethylnitrosamine (2mg/kg). These doses were chosen to minimize effects due to toxicity. 2. Two methods of extraction and purification of RNA were used and an analysis of the radioactivity present was made by column chromatography of acid hydrolysates of the purified RNA. 3. The extent of methylation of guanine, the principal site of alkylation in rat liver RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

1973
1973
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 19 publications
1
8
1
Order By: Relevance
“…RNA studies described previously have demonstrated radioactive labelling of the -j purine bases via the 1-carbon pool (Craddock and Magee, 1963;Whittle, 1969;McElhone et al, 1971). In the present work metabolic labelling of DNA (expressed as dpm/,umol of purine bases) was 5-6 times less ( Fig.…”
Section: Mletabolic Labelling Of Dnasupporting
confidence: 55%
See 3 more Smart Citations
“…RNA studies described previously have demonstrated radioactive labelling of the -j purine bases via the 1-carbon pool (Craddock and Magee, 1963;Whittle, 1969;McElhone et al, 1971). In the present work metabolic labelling of DNA (expressed as dpm/,umol of purine bases) was 5-6 times less ( Fig.…”
Section: Mletabolic Labelling Of Dnasupporting
confidence: 55%
“…In the present work metabolic labelling of DNA (expressed as dpm/,umol of purine bases) was 5-6 times less ( Fig. 7a and b) than in the corresponding rRNA study (McElhone et al, 1971). In DNA, thymine, and not cytosine, was also labelled by this process (Fig.…”
Section: Mletabolic Labelling Of Dnacontrasting
confidence: 46%
See 2 more Smart Citations
“…The interaction of AGO2 with the rRNA is drastically reduced when cells are treated briefly with actinomycin D, which impairs Pol I transcription (34,35). This drug treatment would not affect the overall ribosomal levels, as their half-lives have been estimated to be up to 5 days (36). Thus, we conclude that interactions between AGO2 and the rRNA occurs at least in part within the nucleus.…”
Section: Discussionmentioning
confidence: 82%